MicroRNA‐146 represses endothelial activation by inhibiting pro‐inflammatory pathways. Issue 7 (3rd June 2013) - Cheng, Henry S.; Sivachandran, Nirojini; Lau, Andrew; Boudreau, Emilie; Zhao, Jimmy L.; Baltimore, David; Delgado‐Olguin, Paul; Cybulsky, Myron I.; Fish, Jason E.
Abstract : Activation of inflammatory pathways in the endothelium contributes to vascular diseases, including sepsis and atherosclerosis. We demonstrate that miR‐146a and miR‐146b are induced in endothelial cells upon exposure to pro‐inflammatory cytokines. Despite the rapid transcriptional induction of the miR‐146a/b loci, which is in part mediated by EGR‐3, miR‐146a/b induction is delayed and sustained compared to the expression of leukocyte adhesion molecules, and in fact coincides with the down‐regulation of inflammatory gene expression. We demonstrate that miR‐146 negatively regulates inflammation. Over‐expression of miR‐146a blunts endothelial activation, while knock‐down of miR‐146a/b in vitro or deletion of miR‐146a in mice has the opposite effect. MiR‐146 represses the pro‐inflammatory NF‐κB pathway as well as the MAP kinase pathway and downstream EGR transcription factors. Finally, we demonstrate that HuR, an RNA binding protein that promotes endothelial activation by suppressing expression of endothelial nitric oxide synthase (eNOS), is a novel miR‐146 target. Thus, we uncover an important negative feedback regulatory loop that controls pro‐inflammatory signalling in endothelial cells that may impact vascular inflammatory diseases. Abstract : miR‐146 microRNA is induced by proinflammatory cytokines and acts to inhibit vascular inflammation by repressing endothelial activation through the inhibition of both transcriptional and posttranscriptional endothelial proinflammatory pathways.